Human interphase chromosomes : biomedical aspects - Vorsanova, Svetlana G.; Iourov, Ivan Y.; Yurov, Yuri B. (Springer New York, 2013)
The beginning of interphase cytogenetics can be attributed to significant advances in human molecular genetics and cytogenetics. Owing to experimental and theoretical research at the interface between cellular and molecular levels of chromosomal organization and function, high-resolution techniques for chromosomal analysis (molecular cytogenetic techniques) have become available. Molecular cytogenetics is a branch of biomedical sciences that explores chromosomes at molecular and single-cell resolutions at all stages of the cell cycle. It also comprises the techniques that operate with either the entire genome or specific DNA sequences to analyze genomic structural and functional variations at chromosomal level. In postgenomic era, molecular cytogenetics has appreciably transformed and has given rise to a new field of genomics, called cytogenomics. As a result, new opportunities have emerged for analysis of human interphase chromosomes in almost all cell types and states at unprecedented resolution. In Human Interphase Chromosomes, the editors have provided an overview of current developments in the study of human interphase chromosomes with a special attention to available molecular cytogenetictechnologies for basic and clinical chromosome research.